2002
DOI: 10.1002/1521-3765(20021004)8:19<4402::aid-chem4402>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Protonic and Electronic Conduction in the Molecular Conductor [2-(2-1H-Benzimidazolyl)-1H-benzimidazolium]–TCNQ

Abstract: The Bingel addition of a trimalonate derived from a chiral, cyclotriveratrylene (CTV)‐based tripodal tether to C60 was reinvestigated. The present use of enantiomerically pure (P)‐ and (M)‐configured CTV units in the tether allowed the isolation of a total of four enantiomerically pure C3‐symmetric tris‐adducts of [60]fullerene (two from each CTV enantiomer). With the support of NMR and UV/Vis spectroscopy, electronic (ECD) and vibrational (VCD) circular dichroism spectroscopic analysis (comparison to ECD data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…On the basis of direct observations, it is believed that quinhydrone crystals generate a neutral semiquinone radical phase under high pressure: the formation of this radical confirms the proton electron transfer 6. Crystals of TCNQ–DABCO,7 a TCNQ–glyoxylate metal complex,8 and TCNQ–benzbiimidazolium9 exhibit an influence on the synchronized motion and fluctuation in the segregated stacking columns of TCNQ (TCNQ=7,7,8,8‐tetracyano‐ p ‐quinodimethane; DABCO=1,4‐diazabicyclo[2.2.2]octane). These motions would also be related to cooperative proton electron transfer.…”
Section: Calculated Values Of Charges and Spin Densities Of Each Monomentioning
confidence: 99%
“…On the basis of direct observations, it is believed that quinhydrone crystals generate a neutral semiquinone radical phase under high pressure: the formation of this radical confirms the proton electron transfer 6. Crystals of TCNQ–DABCO,7 a TCNQ–glyoxylate metal complex,8 and TCNQ–benzbiimidazolium9 exhibit an influence on the synchronized motion and fluctuation in the segregated stacking columns of TCNQ (TCNQ=7,7,8,8‐tetracyano‐ p ‐quinodimethane; DABCO=1,4‐diazabicyclo[2.2.2]octane). These motions would also be related to cooperative proton electron transfer.…”
Section: Calculated Values Of Charges and Spin Densities Of Each Monomentioning
confidence: 99%
“…12 These geometries are in accordance with the systematic survey of the correlation between O-H and O• • • O lengths in hydrogen bonds for a large number of material systems. [16][17][18] Proton dynamics in such short intermolecular hydrogen bonds play essential roles in various functional molecular materials such as organic ferroelectrics [19][20][21][22] , molecular conductors [23][24][25] , and biochemical reactions. 26,27 In general, the shape of the potential for hydrogen in short hydrogen bonds is sensitive to the O• • • O distance.…”
Section: Introductionmentioning
confidence: 99%
“…As strong electron acceptors, tetracyanoethylene (TCNE) and 7,7,8,8‐tetracyanoquinodimethane (TCNQ) are of interest in the fabrication of optical and electrical recording,5 energy and data storage,6 sensors,7 and electrochromic and magnetic devices. [8] Their derivatives have been seen to form charge‐transfer (CT) complexes9 and salts,10 some of which exhibit high electronic conductivity and magnetic phenomena 11. It has been reported that the reaction of electron‐rich alkynes with TCNE afforded [2+2] cycloaddition products, which gave 1,1,4,4‐tetracyano‐1,3‐butadienes (TCBD) in high to quantitative yields 12…”
Section: Introductionmentioning
confidence: 99%